ANALISIS PERFORMA SISTEM PELACAKAN ROBOT BERODA BERBASIS ROTARY ENCODER DENGAN MIKROKONTROLER ARDUINO - Siratullah Ahmad (PULSE — Journal of Energy, Informatics & Biomedicine, 2026)
This study presents a performance analysis of a wheeled robot tracking system utilizing rotary encoders for position and orientation sensing. The system, built around an Arduino Uno microcontroller, is designed to provide real-time location mapping and trajectory tracking. The research addresses the challenge of accurate indoor robot navigation by integrating data from two rotary encoders mounted on the robot's wheels. The methodology involves developing an odometry algorithm to calculate the robot's position based on wheel rotations. The data, including distance, speed, and heading, is then transmitted to a computer for visualization and control via a LabVIEW graphical user interface. Experimental results demonstrate the system's ability to effectively track the robot's path, with detailed performance metrics analyzed to evaluate accuracy and precision under various movement conditions. The findings indicate that the system provides a reliable and cost-effective solution for basic mobile robot localization, laying the groundwork for more complex autonomous navigation applications.